Active Cycle of Breathing Technique pada Pasien Penyakit Paru Obstruktif Kronik: Analisis Penerapan Evidence-Based Nursing Practice - Apriani, Nuni; Rayasari, Fitrian; Anggraini, Dewi; Atun, Sri (Universitas Faletehan, 2023)
Acute exacerbation in chronic obstructive pulmonary disease (COPD) is characterized by increased production and accumulation of mucus which aggravates clinical symptoms. One of interventions well-known effectively overcoming airway clearance problem is active cycle of breathing technique. The aim of implementing evidence-based nursing practice was to determine the effectiveness of the active cycle of breathing technique on sputum production in COPD patients. The search for evidence was carried out by PICO (problem, intervention, comparison, and outcome) analysis. 18 COPD inpatients and outpatients were selected based on inclusion and exclusion criteria and were given the intervention. Sputum production was measured before and after it. The data analysis was carried out using Wilcoxon with a p value of 0.014 which showed that there was a difference in the amount of sputum production before and after the intervention. The researchers concluded that active cycle of breathing technique is an effective intervention in overcoming airway clearance problems in COPD patients.